Magnetic Susceptibility Record in Paleozoic Succession (Rhenohercynian Massif, Northern Europe) – Disentangling Sea Level, Local and Diagenetic Impact on the Magnetic Records - Pas, Damien; Da Silva, Anne-Christine; Poulain, Geoffrey; Spassov, Simo; Boulvain, Frédéric (Frontiers in Earth Science, 2019)
This study uses an integrated approach, including sedimentology, geochemistry and hysteresis magnetic measurements on a million year Givetian sequence in the southern margin of the Ardennes carbonate platform (France) to test the reliability of magnetic susceptibility () records as inter-regional correlation tools in remagnetized settings. Furthermore, we aim to better understand the N-S depositional variations and sea-level fluctuations in the Ardennes. Sedimentological analyses revealed a complex platform evolution displaying a variety of shallow- and off-reef paleoenvironmental rocks, which ultimately allowed us to improve the sedimentological model of this area and to constrain the main sea-level fluctuations within the southern margin of the Ardennes platform. Comparison of the  curve of this succession with previously published time-equivalent records in the western margin of the platform indicates a clear correlation between the two areas, despite the distance between the locales, their different sedimentology background and the remagnetization affecting the entire region. In contrast, the comparison of these  profiles from the Ardennes (SW Rhenohercynian Massif, Belgian and France) with coeval data from the Rheinisches Schiefergebirge (NE Rhenohercinian Massif, Germany) do not show obvious correlations. Therefore, it is inferred that syn-sedimentary autogenic processes (e.g., vicinity to landmasses, wave agitation), which operate at small spatial and temporal scales affected the  signal and could cause the lack of correlation between  profiles.